Thermodynamic studies on adsorption of Bovine Serum Albumin (BSA) using nitrocellulose membrane: artricle - Abdul Rahman, Nadhratul Nur Ain; Ideris, Norhidayah (2017)
Thermodynamic studies on adsorption of Bovine Serum Albumin (BSA) protein from aqueous solution by using nitrocellulose (NC) membrane was investigate in this study. Nitrocellulose membrane has been choose as adsorbent due to high tensile strength and hydrophilicity, excellent handling in ensuring that membrane will not rip and detergent free. In this study, characterization of NC membrane was studied by using Attenuated Total Reflected and Fourier Transform Infrared Spectroscopy (ATR-FTIR). Moreover, thermodynamic studies on adsorption of BSA protein on NC membrane was investigated and show that this process was not spontaneous reaction and endothermic. The standard Gibbs free energy (∆r Gᴽ)), the change in standard enthalpy (∆r Hᴽ)) and standard entropy (∆r Sᴽ) was calculated. The result of ∆r Gᴽ) value for 298K, 308K and 318K were 6491.24 J/mole, 3047.25 J/mole and 660.96 J/mole respectively. The results for ∆r Hᴽ) was 64790.17 J/mole and ∆r Sᴽ) shows that 198.24 J/mole. K.